STUDY OF LENGTH AND NUMBER OF PROPELLER INFLUENCE TO ELECTRICAL POWER EFFICIENCY AT WIND POWER STATION - GUNTORO (NIM: 20206045); Pembimbing: Dr. Eng. Suprijadi, WAGITO
Wind energy can be converted to become giration mechanical energy by using propeller at wind turbine rotor. To yield electric energy, hence the rotor attributed to dynamo. In this research, the source of wind used is Fan Cosmos 16-SO33 having diameter around 40 cm. The research method is experimental method while the wind turbine type applied is Horizontal Axis Wind Turbines ( HAWT). The propeller applied is from fiber material with constant width 3,7 cm, length 15 cm, 20 cm, 25 cm, 30 cm, 35 cm, 40 cm and number of propellers : 2, 3 , 4 , 5, 6, 7, 8. In this research it's obtained that the length and the number of propeller influence the electrical power and efficiency yielded. For constant resistance R = 98,3 ohm, the highest electrical power efficiency obtained from 5 propellers with each length 15 cm is n = 23,272 %. This research can be applied in research and contextual based learning ( RBL and CTL) for students in SMA/MA, because there are many physics concepts explained in this research such as wind energy conversion, Bernoulli's Law, moment of inertia, motion of giration, and Faraday's Law.